2016
DOI: 10.1016/j.quascirev.2016.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Holocene climate change in Arctic Canada and Greenland

Abstract: This synthesis paper summarizes published proxy climate evidence showing the spatial and temporal pattern of climate change through the Holocene in Arctic Canada and Greenland. Our synthesis includes 47 records from a recently published database of highly resolved Holocene paleoclimate time series from the Arctic (Sundqvist et al., 2014). We analyze the temperature histories represented by the database and compare them with paleoclimate and environmental information from 54 additional published records, mostly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
176
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 199 publications
(198 citation statements)
references
References 206 publications
(255 reference statements)
10
176
0
1
Order By: Relevance
“…Recently, Lecavalier et al (2017) suggested that the timing of the HTM is earlier (11-10 ka BP) on Ellesmere Island, based on elevation-corrected records of summer melt and water isotopes-at that same location our merged product suggests maximum HTM warmth to occur around 9.5 ka BP (Figure 2h). Our data-model merged product suggests HTM summer temperatures over Greenland are roughly 3.3 ∘ C above modern day-lower than melt-based reconstructions from Ellesmere Island (Lecavalier et al, 2017) of more than 5 ∘ C but in good agreement with the HTM reconstruction by Briner et al (2016) of 3 ± 1 ∘ C. Our data-model merged product suggests HTM summer temperatures over Greenland are roughly 3.3 ∘ C above modern day-lower than melt-based reconstructions from Ellesmere Island (Lecavalier et al, 2017) of more than 5 ∘ C but in good agreement with the HTM reconstruction by Briner et al (2016) of 3 ± 1 ∘ C.…”
Section: Evaluating the Gis Surface Temperature Fieldssupporting
confidence: 65%
“…Recently, Lecavalier et al (2017) suggested that the timing of the HTM is earlier (11-10 ka BP) on Ellesmere Island, based on elevation-corrected records of summer melt and water isotopes-at that same location our merged product suggests maximum HTM warmth to occur around 9.5 ka BP (Figure 2h). Our data-model merged product suggests HTM summer temperatures over Greenland are roughly 3.3 ∘ C above modern day-lower than melt-based reconstructions from Ellesmere Island (Lecavalier et al, 2017) of more than 5 ∘ C but in good agreement with the HTM reconstruction by Briner et al (2016) of 3 ± 1 ∘ C. Our data-model merged product suggests HTM summer temperatures over Greenland are roughly 3.3 ∘ C above modern day-lower than melt-based reconstructions from Ellesmere Island (Lecavalier et al, 2017) of more than 5 ∘ C but in good agreement with the HTM reconstruction by Briner et al (2016) of 3 ± 1 ∘ C.…”
Section: Evaluating the Gis Surface Temperature Fieldssupporting
confidence: 65%
“…ka BP (Wagner & Bennike 2015). The timing of peak warmth agrees well with the average temperature trend across Greenland as compiled by Briner et al (2016). ka BP at 95 cm depth (the lowermost sample above the reworked zone 1) to c. 5.4 cal.…”
Section: Holocene Palaeoenvironmental History Of Trifna Søsupporting
confidence: 79%
“…Mean summer insolation at 80°N was approximately 50 W m À2 higher during the Early Holocene (Greenlandian) insolation maximum compared to today and resulted in the Early to Middle Holocene thermal maximum (HTM) causing retreat and disappearance of the northern ice sheets except for the Greenland Ice Sheet (Berger & Loutre 1991;Ullman et al 2015). The recent compilation by Briner et al (2016) highlighted that the expression of the HTM and subsequent cooling is locally offset by up to c. 2 ka, but overall warming in North and East Greenland was more pronounced and preceded warming in southwest Greenland. The recent compilation by Briner et al (2016) highlighted that the expression of the HTM and subsequent cooling is locally offset by up to c. 2 ka, but overall warming in North and East Greenland was more pronounced and preceded warming in southwest Greenland.…”
mentioning
confidence: 99%
“…This aligns with peak cooling onset times in the region between 6 and 5 ka (Figure 2e). 4-3 ka) is also the Holocene minimum extent of the Greenland Ice Sheet, with Neoglacial growth of the ice sheet beginning around this time (Briner et al, 2016). 8-7 ka) intervals of maximum warmth, whereas those to the south or west experienced peak warmth ca.…”
Section: Acceleration Of Holocene Coolingmentioning
confidence: 96%